INVESTIGATION OF THE TRIBOLOGICAL PROPERTIES OF A METAL-POLYMER BASED ON ULTRA-HIGH MOLECULAR WEIGHT POLYETHYLENE AND PREDICTION OF ITS DURABILITY IN TRIBOLOGICAL JOINTS - Popil, Oleg; Yeriomina, Yekaterina; Shurpik, Vladislav; Yarovyi, Yaroslav (Problems of Friction and Wear, 2026)
The article presents the results of scientific research on the processes of operation of a polymer composite material based on ultra-high molecular weight polyethylene, containing 20 wt.% binary alloy of the Al-Cr system as a filler in a tribological joint. The influence of sliding speed and load on the wear intensity and coefficient of friction of the polymer composite was determined, and mathematical models were developed. They describe its tribotechnical behaviour depending on the load and sliding speed of the friction unit. The obtained mathematical dependencies allow us to reliably predict the service life of the composite in tribological joints of equipment and mechanisms of modern machinery, which is important for increasing their efficiency and reliability.